TINJAUAN PENERAPAN STANDAR GROOMING FRONT OFFICE DI HOTEL THE AXANA PADANG - Tambuanan, Novia Kristina; Kasmita, Kasmita; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of research is theapplication observation grooming standard front office in The Axana Hotel Padang City. This research consists of five indicators are: personal hygiene, attitude, greeting, polite, welcome guest. This type of research is descriptive research using survey method. Population in this research is guest have stayed and visit inThe Axana Hotel Padang on January 2014 until Desember 2014 amounted to 20.543 guest. Sampling technique is non probability sampling, using insidental sampling. Sample number in this research amounted to 95 guest. Data collection using a questionnaire based on a Likert scale that tested for validity and reliability. Based on the results of the study concluded that in general the application observation grooming standard front officeinThe Axana Hotel Padang City good less in mean 90,41 between range 70 -< 93, and for allindicators about grooming standardgood less all.Key Word: Grooming Standar, Employee, Front Office, Guest